A Randomized Clinical Trial of Regdanvimab in High-Risk Patients With Mild-to-Moderate Coronavirus Disease 2019. (8th August 2022) - Kim, Jin Yong; Săndulescu, Oana; Preotescu, Liliana-Lucia; Rivera-Martínez, Norma E; Dobryanska, Marta; Birlutiu, Victoria; Miftode, Egidia G; Gaibu, Natalia; Caliman-Sturdza, Olga; Florescu, Simin-Aysel; Shi, Hye Jin; Streinu-Cercel, Anca; et al.
Abstract: Background: We evaluated clinical effectiveness of regdanvimab (CT-P59), a severe acute respiratory syndrome coronavirus 2 neutralizing monoclonal antibody, in reducing disease progression and clinical recovery time in patients with mild-to-moderate coronavirus disease 2019 (COVID-19), primarily Alpha variant. Methods: This was phase 3 of a phase 2/3 parallel-group, double-blind, randomized clinical trial. Outpatients with mild-to-moderate COVID-19 were randomized to single-dose regdanvimab 40 mg/kg (n = 656) or placebo (n = 659), alongside standard of care. The primary endpoint was COVID-19 disease progression up to day 28 among "high-risk" patients. Key secondary endpoints were disease progression (all randomized patients) and time to recovery (high-risk and all randomized patients). Results: Of 1315 randomized patients, 880 were high risk; the majority were infected with Alpha variant. The proportion with disease progression was lower (14/446, 3.1% [95% confidence interval CI, 1.9%–5.2%] vs 48/434, 11.1% [95% CI, 8.4%–14.4%]; P < .001) and time to recovery was shorter (median, 9.27 days [95% CI, 8.27–11.05 days] vs not reached [95% CI, 12.35–not calculable]; P < .001) with regdanvimab than placebo. Consistent improvements were seen in all randomized and non-high-risk patients who received regdanvimab. Viral load reductions were more rapid with regdanvimab. Infusion-related reactions occurred in 11 patients (4/652 [0.6%] regdanvimab, 7/650 [1.1%] placebo). Treatment-emergent serious adverse events were reported in 5 of (4/652 [0.6%] regdanvimab and 1/650 [0.2%] placebo). Conclusions: Regdanvimab was an effective treatment for patients with mild-to-moderate COVID-19, significantly reducing disease progression and clinical recovery time without notable safety concerns prior to the emergence of the Omicron variant. Clinical Trials Registration: NCT04602000; 2020-003369-20 (EudraCT). Abstract : Compared with placebo, regdanvimab effectively reduced the rate of disease progression, shortened time to recovery and more rapidly reduced viral load in patients with mild-to-moderate SARS-CoV-2 alpha variant at high risk of progression to severe disease. No notable safety concerns were observed.